Efficacy of Lockdowns in Africa - Daglous Makumbe (Journal of BRICS Studies)
The novel coronavirus has rocked the world, unleashing disease, deaths and a social quagmire. The catastrophic implications of the pandemic have pushed states on the brink forcing most of them to institute country lockdowns in a bid to flatten the curve of infections, avoid new ones and ensuring that the health systems are not overwhelmed at any one point in time. More than ninety per cent of states went on lockdowns, leading to corrosive effects on their economies. The death toll in Asia and Europe was astronomical, whilst that of the United States of America, Brazil and India was unprecedented. Except for a few countries in Europe and Africa that did not act homogeneously, the rest of the world ceased to function. Whilst lockdowns were effective in western countries, in the African continent, it was a different case. Although there was a willingness to institute lockdowns in Africa, the context made it almost impossible for many countries to effectively and efficiently do so. These factors which hampered the workability of lockdowns included high informal employment rates, informal settlements, rampant homelessness, porous borders, a high population density, institutions with vulnerable populations as well as conflict settings. This paper discusses in detail the research findings of the author on the efficacy of lockdowns in Africa utilising the idealism theory. The importance of the study is to equip policymakers with better strategies to make lockdowns more effective through the dissection of problems discovered in the research findings. The paper’s findings are that lockdowns are difficult to adhere to in the African context, should be context-bound and must be buttressed by government efforts and interventions for them to be effective.